A chalcone‐based fluorescent chemosensor for detecting Mg2+ and Cd2+. (29th December 2021) - Park, Soyoung; Suh, Boeon; Kim, Cheal
Abstract: SBOD (sodium (E)‐2‐(3‐[5‐bromothiophen‐2‐yl]‐3‐oxoprop‐1‐en‐1‐yl)‐4, 6‐dichlorophenolate) was designed and synthesized as a chalcone‐based fluorescent turn‐on chemosensor for Mg 2+ and Cd 2+ . SBOD selectively detected Mg 2+ and Cd 2+ through the increase in effective fluorescence. Detection limits of SBOD for Mg 2+ and Cd 2+ were calculated to be 3.8 μM and 2.9 μM, respectively. The binding modes of SBOD for Mg 2+ and Cd 2+ were determined to be 1:1 by ESI‐MS and Job plot. Association mechanisms for SBOD to Mg 2+ and Cd 2+ were illustrated by ESI‐MS, UV–vis, fluorescence spectroscopy, and calculations. Abstract : A chalcone‐based fluorescent chemosensor SBOD was used as a significantly useful fluorescence sensor for specific detection of Mg 2+ and Cd 2+ . Interestingly, the colour change of solutions could be used to distinguish SBOD ‐Mg 2+ and SBOD ‐Cd 2+ . In particular, the SBOD probe is the first example of simultaneous sensing of both Mg 2+ and Cd 2+ . The sensing mechanisms for SBOD ‐Mg 2+ and SBOD ‐Cd 2+ were elucidated based on ESI‐MS, 1 H NMR titrations, calculations, fluorescence, and UV–visible titration.